A time to reflect: deviations from the balanced time perspective are associated with hypomentalization - Winquist, Anne; Rönnlund, Michael (Frontiers in Psychology, 2024)
Poor mentalization, or lack of capacity to reflect on self and others in terms mental states, thoughts, and feelings, and time perspective biases were both related to mental disorders and lower wellbeing in separate studies. Expanding one prior study, we examined the relationship of mentalization and time perspective, including a measure known as deviations from the balanced time perspective (DBTP) that summarizes time perspective biases across the past, present, and future time frames.Functioning Questionnaire (RFQ-8) and a six-dimensional version of the Zimbardo Time Perspective Inventory (S-ZTPI). Given recent evidence that the original two-factor structure of the RFQ may need to be reconsidered, we used confirmatory factor analyses (CFA) to compare alternative models for RFQ as a first step.In line with several recent studies, the CFA favored a unitary model of RFQ-8 reflecting hypomentalization (or uncertainty). The total score showed significant associations with Past Negative, Present Fatalistic, and Future Negative dimensions of S-ZTPI, while hypomentalization was negatively associated with Future Positive. Of major interest, DBTP and hypomentalization showed a strong positive correlation (r = 0.64 for latent constructs; r = 0.62 in an adjusted model).Conclusions: Deviations from the balanced time perspective were substantially related to hypomentalization. Further research is required to examine the generalizability of the finding (e.g., to measures of mentalization focused on others) and to provide a better understanding of the theoretical basis of the link. Potentially shared associations in development (e.g. attachment style) and mindfulness, that may influence both time perspective and mentalization is of interest in this regard.